ASEN free trade agreement a key step toward economic integration for Vietnam from the perspective of complementary trade - Nguyen, Phuong Thi Mai (KDI School, 2011)
The thesis focuses on the reasons and motivations to initiate ASEAN ? Free Trade Area Agreements in the context of the global tendency of economic regionalization through examining Vietnam’s economy from its process of building and applying mutually-recognized agreements. The current issue is all ASEAN economies are negotiating bilateral economic agreements by their own, at the same time with taking ASEAN approach with other economic powers in the world. However, the realization of the ASEAN Free Trade Area has not lessened the importance of ASEAN’s economic partners. ASEAN’s countries have promoted economic linkages through ASEAN-plus FTA toward integrating the ASEAN region with global economy. In this thesis, I want to examine Vietnams’ earlier regional integration in AFTA by dividing into 2 parts. Firstly, the thesis presents an overview of ASEAN FTAs from Vietnam’s perspective. From that point of view, the aim of the thesis is to answer a big question on how important it is for Vietnam to accelerate the implementation of AFTA. Secondly, I want to review Vietnam’s efforts in initiating ASEAN Free Trade Agreements by analyzing what we have done, what we have achieved in every stage both in economies and in politics. The comprehensive cooperation of ASEAN plus shows that such progress has brought about positive trade effects between ASEAN and other partners, especially important, has motivated the economy of each member country in South East Asia. So as Vietnam in particular, has actively taken part in the economic integration in the world economy. It can be considered as a significant way of maintaining the momentum of regional economic integration which means sending a positive signal to the outside world that Vietnam is not slowing down on intra-regional liberalization commitments because of the economic crisis. In conclusion, through those arguments, this thesis also shows that ASEAN ? Free Trade Agreement is as a key step toward economic integration for Vietnam. In hence, the purpose of assessing the prospects of Vietnamese economic integration to ASEAN from 2001 to present is ambitiously completed.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: ASEN free trade agreement.; Vietnam.